A comparison of the pacing profiles adopted by male runners in the Comrades Marathon up run - Manchip, Genine (Department of Human Biology, 2025)
Introduction Ultramarathon running is gaining popularity worldwide. Due to the difficulty in completing an ultramarathon, knowledge of the most effective pacing to adopt in an ultramarathon race would be invaluable to coaches and runners, as well as of academic interest, since this information is already well established for the standard marathon. The Comrades Marathon is a globally recognised ultramarathon that takes place in South African annually. Its history and difficult undulating route attracts runners of all abilities, from around the world. Adopting the most effective pacing strategy to complete the Comrades Marathon would optimise the performance of a runner and thereby lead to each being more likely to achieve their specific goal. Aims and Objectives The aim of this study was to analyse the race results of three years of the Comrades Marathon “up” runs, namely 2015, 2017 and 2019 and to compare the pacing profiles of the fastest through to the slowest male runners in the field. The objectives of this study were 1.) To analyse the race results of the Comrades Marathon “up” run to identify the pacing profiles adopted by the fastest male runners, through to the slower runners; 2.) To compare the pacing profile of the top 10 male runners in each year, relative to their most recent standard marathon pace. Methods The study utilised a retrospective design. The study sample included the Comrades Marathon race results over three years of consecutive “up” runs. Only male runners, irrespective of age, were included in the study. If runners featured in more than one race, only their fastest finish time was included in the sample for statistical analysis. Runners were excluded from the study if there were split (intermediate) times missing or if their data was incomplete in some way. In the second part of the study, runners in the top 10 were excluded if their most recent standard marathon time could not be established. Results A total of 22 199 male runners were included for data analysis. The data was divided into quartiles, based on finishing time. This resulted in four groups, separated by 1.67-hour intervals. The first group contained the smallest number of participants (n=503) which was only 2.3% of the field and the last quartile (group) contained the most runners at 50.3% of the field (n= 11181). There was a significant difference between groups one, two, and four in the pacing profile when speed through the race segments was normalised to the speed at which the first segment was run. This was also the case when speed through each segment was normalised to mean race pace (of the entire race). All four groups showed a parabolic pacing profile; specifically a reverse “J“-shaped, when race pace was normalised to both mean race speed and to speed of the first segment. Analysis of the elite runners (top 10) for each year, showed that these runners started at an average of 88% of their marathon pace and averaged 80-90% of their marathon pace throughout the race. The elite runners showed a positive pacing profile with moderate effect. Conclusion This study showed that there is no significant difference between the pacing profiles of the faster male runners versus slower male runners. Runners adopted a reverse “J”-shaped pacing profile when their pace at different points in the race was compared relative to their mean race pace, or when each segment was compared to the pace in the first segment of the race. This finding is similar to previous studies that found that the most efficient pacing profile in recreational ultramarathon and marathon runners is a parabolic shaped profile. The elite runners' Comrades Marathon started the race at an average of 88% of their marathon pace and maintained an average pace of 80-90% of their standard marathon pace, throughout the race.